Decisions on innovation and diffusion and the limits of deregulation - Hubner, Heinz (Technovation)
Governments in Western Europe are currently assigning responsibilities for functions of high societal importance to private groups under the slogan 'Deregulation and privatization'. Identical principles are applied in former communist countries in Eastern Europe, based on the thesis that only free-market mechanisms will guarantee most benefits for all groups of society. Against this thesis, governments in most industrialized states have established so-called 'national innovation systems', formed by government-owned or -supported research institutions and measures supporting the innovation abilities of companies, since competition in innovation has become the most important kind of competition on company level and between national economies. The main aims of the article are to reach an understanding of mechanisms and responsible actors for generation and diffusion of innovation within a society and (national) economy; to demonstrate problems and impacts of unreflected deregulation and privatization is not in conformity with, but opposed to, economic theory as founded by Adam Smith; and to derive consequences and measures necessary for coordination within an economically developed society. The research methodology includes the use of an explanatory model, demonstration of examples, partly based on our own research, exergesis, and logical final conclusion.